In vivo therapeutic evaluation of phage cocktail and probiotic in reducing Salmonella infection in Broilers - KUMAR, TARUN; RAJORA, V S; ARORA, NIDDHI; MITTAL, DINESH; PRASAD, AMIT (The Indian Journal of Animal Sciences, 2023)
Antimicrobial resistance and ban on the usage of most of the antibiotics in food producing animals especially in poultry and pigs propelled research towards antibiotic alternatives. Food borne and multidrug-resistant (MDR) pathogens like Salmonella can enter food chain via consumption of the contaminated meat. Bacteriophage (phage) therapy could be used during rearing or pre-harvest stages of poultry production to overcome these emerging problems. The present study was conducted to determine the therapeutic effectiveness of bacteriophage cocktail and probiotics against Salmonella gallinarum in experimentally infected broiler chicks based on mortality, clinical manifestations, and faecal shedding. In vitro evaluation revealed that optical density (OD) of Salmonella gallinarum at MOIs of 102 was significantly reduced by individual phages as well as phage cocktail, with comparably less decrease in optical density in the culture treated with individual phage than the phage cocktail. Bacteriophage cocktail with concentration 1011 PFU/ml was able to protect 100% birds infected with Salmonella gallinarum. Faecal shedding rate was significantly low in the birds treated with bacteriophage cocktail and probiotics (1.2%) than untreated group. Significant improvement in body weight was seen in the bacteriophage treated groups as compared to untreated infected group. Based on the findings of the current study, administering high titre bacteriophages alone or in combination with probiotics for the effective management of Salmonella infection in broiler chicks may be suggested as an alternative to antibiotics as well as a useful strategy to control food borne pathogens in the food chain.